2015
DOI: 10.11648/j.ajac.20150306.17
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Isotopic Abundance Ratio of <sup>13</sup>C, <sup>2</sup>H, and <sup>18</sup>O in Biofield Energy Treated Ortho and Meta Toluic Acid Isomers

Abstract: O-Toluic acid (OTA) and m-toluic acid (MTA) are two isomers of toluic acid that act as an important organic intermediates, mostly used in medicines and pesticides. The aim of the study was to evaluate the impact of biofield energy treatment on isotopic abundance ratios of 2 H/ 1 H, 13 C/ 1 2C, (PM+1)/PM and 18 O/ 16 O, (PM+2)/PM, in toluic acid isomers using gas chromatography-mass spectrometry (GC-MS). The OTA and MTA samples were divided into two parts: control and treated. The control sample remained as unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The relative intensity of the peak in the mass spectra is directly proportional to the relative isotopic abundance of the molecule and the isotopic abundance ratio analysis was followed by the scientific literature reported [36][37][38][39] method described as below: P M stands for the relative peak intensity of the parent molecular ion [M + ] expressed in percentage. In other way, it indicates the probability to A elements having only one natural isotope in appreciable abundance (for e.g.…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The relative intensity of the peak in the mass spectra is directly proportional to the relative isotopic abundance of the molecule and the isotopic abundance ratio analysis was followed by the scientific literature reported [36][37][38][39] method described as below: P M stands for the relative peak intensity of the parent molecular ion [M + ] expressed in percentage. In other way, it indicates the probability to A elements having only one natural isotope in appreciable abundance (for e.g.…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
“…Consequently, the percentage change in the isotopic abundance ratio of P M+2 /P M was significantly increased by 29.18% in the Biofield Energy Treated sample compared with the control sample. Thus, 13 Scientific literature [37][38][39]45] reported that the vibrational energy is closely related with the reduced mass (µ) of the compound and the alteration of the vibrational energy can affect the several properties like physicochemical, thermal properties of the molecule. The relation between the vibrational energy and the reduced mass (µ) for a diatomic molecule is expressed as below [42,45]…”
Section: Isotopic Abundance Ratio Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This process is known as The Trivedi Effect ® -Biofield Energy Healing Treatment [15,16] [17]. Biofield Energy Treatment (The Trivedi Effect ® ) has been extensively studied with significant outcomes in many scientific fields such as agriculture [18][19][20], biotechnology [21][22][23], materials science [24][25][26][27][28], pharmaceutical sciences [29][30][31], medical science [32,33], and microbiology [34][35][36]. Literature demonstrated that Biofield Energy Healing Treatment (The Trivedi Effect ® ) might be an alternative method for increasing or decreasing the natural isotopic abundance ratio of the substances [37,38].…”
Section: Introductionmentioning
confidence: 99%